Peranan Kepuasan Kerja Pada Karyawan PT. Bank Syariah Mandiri KCP Manado Pasar 45 - Djangkarang, Sri M.; Areros, William Agustinus; Runtuwene, Roy F. (Sam Ratulangi University, 2019)
The purpose of this study was to determine the differences in job satisfaction between permanent employees and contract employees. The benefits of this research so that it can become one of the information for all relevant parties and provide input for the company in an effort to improve employee job satisfaction. The research location was conducted at PT. Bank Mandiri Syariah Bank KCP Manado Pasar 45 where the company is one of the companies engaged in banking services. This research is comparative research and uses data collection methods in the form of job satisfaction scales. Based on the results obtained in this study, the significance value is 0.335 which indicates that 0.335 5 0.05 so that the hypothesis is accepted, there is a difference in the level of job satisfaction between permanent employees and contract employees. Then the test results of the difference in mean values of contract employees get a value of 114.70 which is greater than permanent employees who only get a mean value of r 106.10. Thus it can be said that the work satisfaction of contract employees is higher in employment in the company or contract employees are more satisfied at work